Correlation of FNAC with Histopathology in the Diagnosis of Differentiated Thyroid Carcinoma - Pervin, Shahnaz; Keya, Shamim Ara; Ullah, Parash (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Fine-needle aspiration cytology (FNAC) is an important diagnostic tool for differentiating between neoplastic and non-neoplastic lesions of the thyroid. The current study was carried out to observe the comparison between preoperative fine needle aspiration cytology (FNAC) and postoperative Histopathology in the diagnosis of Differentiated Thyroid Carcinoma. Methods: This cross-sectional observational study was conducted in the department of Pathology, Rajshahi Medical College (RMC), Bangladesh from January 2019 to December 2020. Clinically suspected and diagnosed by FNAC, a total of forty patients of differentiated thyroid carcinoma attending outpatient and inpatient department of Otolaryngology, RMCH were enrolled in this study. Biopsy material was examined for histopathological diagnosis. Results: In this study, out of forty cases, 35 were papillary and 5 were follicular carcinoma. Mean age was 25.48+9.70 years and Male: Female was 1:6. Among 40 cases of FNAC findings, 33 cases (82.5%) were classic papillary carcinoma, 01(2.5%) case was follicular variant of papillary carcinoma, 5 cases were (12.5%) were follicular lesion and 01(2.5%) case was nodular goitre. Among 40 cases of histopathological findings, 32(80%) cases were classic papillary carcinoma, 03(7.5%) were follicular variant of papillary carcinoma and 5 cases were follicular carcinoma. In histopathological findings, none of them was nodular goitre. So, all FNAC findings were consistent with histopathological findings except nodular goitre which was diagnosed as classic papillary carcinoma in histopathology. Conclusion: FNAC is a safe and relatively accurate method for preoperative evaluation of thyroid malignancy before surgery. Therefore it is a reliable diagnostic test for evaluation of thyroid carcinoma. J Shaheed Suhrawardy Med Coll 2022; 14(1): 28-31